Building an Entrepreneurial Ecosystem: Insights into Effective Management Practices in Vocational Schools - Yudistiro Bakti, Daud Kurniadi; Pratama, Ari Yoga; Yousaf, Esha Momena (Development: Studies in Educational Management and Leadership, 2024)
This research aims to discover data and the concept of an educational institution regarding entrepreneurship education in vocational schools, which plays a crucial role in shaping a workforce with the skills to enter the job market. It seeks to understand the vision and mission of vocational schools. The research employs a qualitative method using library studies. Data is collected through relevant references such as journals, the internet, and articles related to the development of entrepreneurship in vocational schools. The results of this research indicate that the working world greatly requires individuals who can develop new ideas in business and possess adequate skills. Vocational education is a supporting factor in producing skilled workforce in their respective fields. Vocational schools have the opportunity to build an economic system by leveraging the development of adolescents at this time, educating students to be interested in becoming entrepreneurs. Entrepreneurship preparation should be emphasized, especially in vocational schools. If the education system and training run effectively, it is possible to produce competent entrepreneurs and reduce unemployment rates. The education sector has the responsibility to create prospective workers with skills and abilities.